1993
DOI: 10.1021/bi00086a033
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and development-specific expression in transgenic mice of a type I procollagen (COL1A1) minigene construct with 2.3 kb of the promoter region and 2 kb of the 3'-flanking region. Specificity is independent of the putative regulatory sequences in the first intron

Abstract: Previous reports have provided inconsistent data as to the cis-regulatory elements that are essential for correct expression of the gene for the pro alpha 1 (I) chain of type I procollagen (COL1A1) in the many tissues in which the protein is synthesized. Here, two internally deleted minigene versions of the human COL1A1 gene were used to prepare transgenic mice. The constructs made it possible to test regulatory sequences in the normal context of the gene. Also, in contrast to the reporter genes used in previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…The use of an ␣1(I) minigene in place of a promoter-reporter gene construct in transfection experiments (40) has averted some of these drawbacks, but even minigenes are limited in the extent to which 5Ј and 3Ј flanking sequences can be represented, and there are possible uncertainties in quantification that can result from differences in the levels of stability of the initial and mature transcripts in comparison with that of Col1A1 mRNA. The results of transgenic experiments have also been controversial (8,35,53,54), in part because of the need to compare different constructs and the possible confounding effects of copy number and site of insertion on expression of the transgene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of an ␣1(I) minigene in place of a promoter-reporter gene construct in transfection experiments (40) has averted some of these drawbacks, but even minigenes are limited in the extent to which 5Ј and 3Ј flanking sequences can be represented, and there are possible uncertainties in quantification that can result from differences in the levels of stability of the initial and mature transcripts in comparison with that of Col1A1 mRNA. The results of transgenic experiments have also been controversial (8,35,53,54), in part because of the need to compare different constructs and the possible confounding effects of copy number and site of insertion on expression of the transgene.…”
Section: Discussionmentioning
confidence: 99%
“…Since some of these elements could be placed in the first intron, numerous studies, using both transfection and transgenic approaches, have been designed to investigate transcriptional regulation by the first intron and to identify possible responsible regulatory elements, but these experiments have resulted in conflicting conclusions (reviewed in reference 8). While some studies have demonstrated a role for the intron in regulation and have identified cis-acting sequences that bind Sp1 and AP1 as important elements (6, 9, 29, 33-35, 44, 51, 52), other studies have indicated that the intron does not regulate expression of the gene (40,53,54). Thus, the role of the first intron in the regulation of the Col1A1 gene remains uncertain and controversial.…”
mentioning
confidence: 99%
“…Because the small amounts ofglycerol in the samples ignited during the first few minutes at 600C, the oven was placed in a fume hood. Preliminary experiments indicated there was no further decrease in weight if samples were incubated at 600C ( 12). As indicated in Fig.…”
Section: Methodsmentioning
confidence: 75%
“…To assay the steady-state levels of mRNA, total cellular RNA was isolated from tissues by extraction with acidic guanidinium thiocyanate-phenol-chloroform ( 1 1). The amount ofmRNA from the transgene relative to the mouse mRNA from endogenous COL 1 Al gene was measured by a quantitative reverse transcriptase (RT)-PCR method ( 12). 1-5 ug of total RNA was reverse transcribed in 20 Ml of reaction mixture using primer BS33 (5'-ATCAAG-TTTGA'3') (200 pmol) for the proal (I) chain and a preamplification system for first-strand cDNA synthesis (SuperScript<>, GIBCO BRL, Gaithersburg, MD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation